2017
DOI: 10.29252/arakmu.11.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Nigella Sativa (Black Caraway (Oil on Oral Dichlorvos Induced Hematological, Renal and Nonspecific Immune System Toxicity in Wistar Rats

Abstract: Background: Exposure to environmental toxins such as organophosphates poses a great threat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Group 1 (control)-were given normal saline (1 ml/kg orally) daily for 14 days Group 2-were given DDVP (8.8 mg/kg orally) daily for 14 days [8,20,21] Group 3-were given CPF (14.9 mg/kg orally) daily for 14 days [9] Group 4-were given DDVP (8.8 mg/kg orally) plus CPF (14 mg/kg orally) daily for 14 days…”
Section: Treatment Schedulementioning
confidence: 99%
See 2 more Smart Citations
“…Group 1 (control)-were given normal saline (1 ml/kg orally) daily for 14 days Group 2-were given DDVP (8.8 mg/kg orally) daily for 14 days [8,20,21] Group 3-were given CPF (14.9 mg/kg orally) daily for 14 days [9] Group 4-were given DDVP (8.8 mg/kg orally) plus CPF (14 mg/kg orally) daily for 14 days…”
Section: Treatment Schedulementioning
confidence: 99%
“…Evidently, increased oxidative damages have been implicated in adversely affecting psychological and cognitive related functions through disruptions of normal neurogenesis in the hippocampus and other potential hotspots within the brain [8,9,[17][18][19]. Chronic and subchronic exposures to both CPF and DDVP have resulted in wide range toxicity, including cardiotoxicity, neurotoxicity, hepatotoxicity, renal toxicity, haematological toxicity, and immune system toxicity among others [8,9,[20][21][22][23]. Besides cholinesterase inhibition, these substances caused marked disruptions in normal oxidative functions [8,9,20,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichlorvos (DDVP), one of the effective OPs used throughout the world, in household and agricultural activities for the control of insects and pests, whose primary mechanism of toxicity is an irreversible inhibition of acetylcholinesterase (AChE) activities, eliciting reproductive toxicity, [6] hematotoxicity, [7] cardiotoxicity, [8] and neurotoxicity [9] in a host of other inevitable damages.…”
Section: Introductionmentioning
confidence: 99%
“…Nigella sativa oil (NSO) is a highly valued medicinal solvent, used traditionally in the treatment of many diseases. Evidence from animal and human studies has shown that the oil of Nigella sativa exhibits extensive pharmacological properties including antioxidant, [12,13] anti-inflammatory, [14] neuroprotective, [12,13,15] immunomodulatory and antitumor, [7,16] efficacy in neurodegenerative diseases [17] and memory enhancing effects. [18] This study evaluated the neuroprotective efficacies of NSO's antioxidant and neurogenic potentials against DDVP induced hippocampal neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%